Design and development of a portable, deployable trolley: part 3 - Du, Xue Zeng (Nanyang Technological University, 2022)
Shopping cart has been used widely by customers to transport goods after purchase. The problem arises when goods purchased need to be shifted to the car boot. This proposed the need for a device that could facilitate easy loading and unloading process. Such a device is modelled as a foldable trolley in this project. Such portable trolleys can be deployed and stowed away easily in a car boot without removing goods that were initially placed inside. Hence, mechanisms that can fold into compact assembly when collapsed and capable of heavy loading when deployed are required. The design process has been separated into two parts, the front leg mechanism design (part 2) and the rear leg design (part 3). This project focus on the rear leg mechanism. With studies and research done on various types of mechanisms, 3 concepts were developed. Autodesk Inventor and Solidworks were used in this project for modelling. Finite element analysis was carried out for force and displacement analysis. A prototype was fabricated for concept 2 and concept 3 for further analysis, and eventually, concept 3 was selected. In collaboration with designs done in part 2, the front leg mechanism, a completed foldable trolley was developed.